DETEKSI PERUBAHAN GARIS PANTAI MELALUI CITRA PENGINDERAAN JAUH DI PANTAI UTARA SEMARANG DEMAK - Parman, Satyanta (Jurnal Geografi, 2014)
The purpose of this study was to assess the coastline changes in north coast ofSemarang-Demak. The research method was used satellite image interpretationof Landsat Image in 1998 and Allos Image in 2006, and field cross-checking. Byoverlaying the two satellite images through a geographic information system todetermine the changes that can occured on the north coast of Semarang-Demak.Based on research results showed that the accuracy obtained by 93% and couldbe valid from 28 observation points that form the shoreline and land use.Shoreline that occurred between 1999 and 2006 experienced more abrasionprocess if compared with accretion. The Advice of this study was to acceleratedetermination of the shoreline changes preferably used remote sensing images, inorder to involved community in preventing any abrasion. The methods could bedone through greening coastal areas, for example by mangroves planting on thebeach.